A Comparative Study Between Nineveh and Tikrit Medical School Teachers Perceptions regarding the Effectiveness of OSCE in Clinical Examination (Indian Journal of Forensic Medicine & Toxicology, 2020)
Assessment students competence is of much importance especially when evaluation the expected learningout come of medical education and because of increasing students number enrolled in medical colleges , thislead to enhance the chance of malpractice that compromise patient conditions , therefore it is challenging todevelop and implement such an objective assessment method in clinical examination. Objective of the study:The study aim is to compare the traditional and innovative medical school teachers perceptions regardingthe effectiveness of OSCE in clinical examination . A descriptive cross sectional study has been conductedin both (Nineveh and Tikrit medical college from the period of 15th February till 20 th April / 2014.The study was included 95 medical teachers from both traditional and innovative schools .( 55 teachersfrom the traditional school and 40 from innovative school). A special questionnaire form was prepared bythe researcher through direct interviewing with the study sample. The results show that 63.1% of medicalteachers are male , 49.5% aged between 40-49 years ,65.3 % from basic specialty sciences , 51.6% havinga period more than 10 years in teaching, 70.9% of traditional school teachers agree that OSCE evaluate thepractical objectives in comparison to 67.5% of innovative school teachers agree with that OSCE evaluateknowledge, understanding , practical , and intellectual objectives. The study concluded that more than halfof traditional medical teachers agree with the affectivity of OSCE in assessing large number of studentswithout bias while medical teachers from innovative school agree with the objectivity of OSCE in clinicalevaluation.
Keywords: Medical teachers, Perceptions, clinical examination, Kirkuk, Iraq